The Na+/H+ Exchanger 3 in the Intestines and the Proximal Tubule of the Kidney: Localization, Physiological Function, and Key Roles in Angiotensin II-Induced Hypertension - Nwia, Sarah M.; Li, Xiao Chun; Leite, Ana Paula de Oliveira; Hassan, Rumana; Zhuo, Jia Long (Frontiers in Physiology, 2022)
The sodium (Na+)/hydrogen (H+) exchanger 3 (NHE3) is one of the most important Na+/H+ antiporters in the small intestines of the gastrointestinal tract and the proximal tubules of the kidney. The roles of NHE3 in the regulation of intracellular pH and acid–base balance have been well established in cellular physiology using in vitro techniques. Localized primarily on the apical membranes in small intestines and proximal tubules, the key action of NHE3 is to facilitate the entry of luminal Na+ and the extrusion of intracellular H+ from intestinal and proximal tubule tubular epithelial cells. NHE3 is, directly and indirectly, responsible for absorbing the majority of ingested Na+ from small and large intestines and reabsorbing >50% of filtered Na+ in the proximal tubules of the kidney. However, the roles of NHE3 in the regulation of proximal tubular Na+ transport in the integrative physiological settings and its contributions to the basal blood pressure regulation and angiotensin II (Ang II)-induced hypertension have not been well studied previously due to the lack of suitable animal models. Recently, novel genetically modified mouse models with whole-body, kidney-specific, or proximal tubule-specific deletion of NHE3 have been generated by us and others to determine the critical roles and underlying mechanisms of NHE3 in maintaining basal body salt and fluid balance, blood pressure homeostasis, and the development of Ang II-induced hypertension at the whole-body, kidney, or proximal tubule levels. The objective of this invited article is to review, update, and discuss recent findings on the critical roles of intestinal and proximal tubule NHE3 in maintaining basal blood pressure homeostasis and their potential therapeutic implications in the development of angiotensin II (Ang II)-dependent hypertension.